Isthilâh Al-Insân fi Sûrah al-Isrâ’ ’Inda Ibn ‘Asyur fi Kitâb At-Tahrîr Wa At-Tanwîr - Ahmad Fadly Rahman Akbar; Andrayu Muana (Studia Quranika, 2018)
Many of the scientists and scholars who examine and explore the human as a unity from all sides. Some scientists pay attention to the scientific side and the others examined in terms of the language contained in the Qur'an. The famous exegetes with the language method he uses in interpreting the word in the Qur'an is Imam At-Thahir Ibn Aysur who wrote the phenomenal exegetical book in his linguistic explanation called "at-Tahrir wa at-Tanwir". According to Ibn 'Asyur term of human in the Surah Al-Isra' is; The term of “bani adam” refers to the glory of man among other, The term of “insan” shows the negative side of the human being, The term of “ins” indicates a conformity with the word jinn in the general sense, The term of “nâs” denotes man's unconventionality regardless of believer and kafir, and the term of “basyar” shows social personality that facilitates human in the process of socializing